REGIONAL LANGUAGE HOMONYMY AS A RHETORICAL STRATEGY OF HUMOR IN DIGITAL MEME DISCOURSE - Adinda Galih Mustika; Fitria Anggraini D; Erwin Salpa Riansi (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
This study aims to analyze the use of homonyms in memes as a digital cultural phenomenon. The research method used is a qualitative method with a semantic approach, namely by exploring homonymous forms that are used to create meaning, humor, and social criticism in meme discourse. The research data was obtained through the collection of Indonesian memes from idntimes.com pages that contain elements of a homonym language game. The analysis was carried out by identifying homonymous words that give rise to ambiguity of meaning and examining the visual and linguistic context that reinforces the effects of humor and social innuendo. The results of the study show that homonyms in memes not only serve as a language game, but also as a rhetorical strategy to convey social criticism in a subtle and witty way. In addition, homonyms have proven to be effective in capturing the audience's attention because they bring out multiple layers of meaning and invite creative interpretations from readers.